Examining the leisure use of a bicycle share program: A case study of YouBike in Taipei. (14th March 2020) - Chen, Li-Hsin; Chancellor, H. Charles
Abstract: In this study, we adopted the extended unified theory of acceptance and use of technology (UTAUT2) to examine the key determinants of leisure use of a bicycle-share program (BSP), using data from an online panel of 348 Taiwanese YouBike members. We found that the BSP's leisure users had different priorities from commuting cyclists, with the former rating social support more important than bicycle infrastructure or facilities. In addition, we found hedonic motivation (i.e., perceived enjoyment) to be a more significant factor in leisure use of YouBike than was extrinsic motivation (i.e., performance expectancy). Habit also predicted leisure use of a BSP. These findings challenge traditional notions that well-constructed bicycle infrastructure is the most important driver of BSP uptake. We conclude the article with a reflection on the potential role of BSPs in renormalizing the image of leisure cycling.